In vitro study: Catechins as depigmenting agents inhibit melanogenesis on B16F0 cells - Widyastuti Widyastuti,, Deddi Prima Putra, Satya Wydya Yenny, Aisyah Elliyanti (Journal of Applied Pharmaceutical Science, 2023)
Catechins are flavonoid compounds that are the main components in gambir plants and are reported to have antioxidant activity. Research on the depigmenting agent effect of gambir catechins has not been done much. Melanogenesis inhibition effect of a compound can be done by looking at the decrease in tyrosinase (TYR) enzyme activity and melanin levels. This study aimed to test in vitro the melanogenesis inhibitory activity of catechins isolated from gambir in cell culture, including testing of cell viability, TYR activity, and decreased levels of melanin in B16F0 cells. The results showed that gambir catechins affect the viability of B16F0 cells without causing toxicity to cells. Increasing the concentration and duration of the test significantly decreased TYR activity and melanin levels in B16F0 cells (p < 0.05). Based on the research conducted, it can be concluded that in vitro gambir catechins have an effect as a depigmenting agent.
Keywords: Flavonoid, mouse melanoma, depigmenting agent, catechin